KOMIK DIGITAL EKONOMI UNTUK GENERASI MILENIAL - Yenni Ernawati (Jurnal Education and Development, 2020)
This development research aims to produce products in the form of digital comics on Central Bank material, Payment Systems and Payment Instruments in the Indonesian economy for class X students of Senior High School at Trawas , Mojokerto Regency; Knowing the feasibility of digital comic products as learning media; and knowing students' responses about digital comics in learning. The model used in the development of the Thiagarajan, Semmel , and Semmel models, which are Four D Models (4-D Models) consisting of define , design , develop , and disseminate . Due to time and cost constraints, Disseminate in this study was not carried out. In this study data collection techniques using a questionnaire. The data obtained are quantitative data and qualitative data. The results of this study indicate that: (1) learning media developed with digital comic models get a value from the results of the material expert validation of 96.5%, which means that this learning media is very feasible to use and effective, (2) digital comic learning media also got the value of the results of the validation of media experts by 87.27%, which means this learning media is very feasible to use and effective, (3) this digital comic learning media also gets a value from the validation of peers by 86.25%, which means the media This learning is very feasible to use and effective, (4) digital comic learning media from student questionnaire responses get very good and good grades.